A Gravity-Driven Membrane Bioreactor in Treating Real Fruit Juice Wastewater: Response Relationship Between Filtration Behavior and Microbial Community Evolution - Dan Song; Haiyao Du; Shichun Chen; Xiaodie Han; Lu Wang; Yonggang Li; Caihong Liu; Wenjuan Zhang; Jun Ma (Membranes)
The issue of environmental pollution caused by wastewater discharge from fruit juice production has attracted increasing attention. However, the cost-effectiveness of conventional treatment technology remains insufficient. In this study, a gravity-driven membrane bioreactor (GDMBR) was developed to treat real fruit juice wastewater from secondary sedimentation at pressures ranging from 0.01 to 0.04 MPa without requiring backwashing or chemical cleaning, with the aim of investigating flux development and contaminant removal under low-energy conditions. The results demonstrate an initial decrease in flux followed by stabilization during long-term filtration. Moreover, the stabilized flux level achieved with the GDMBR at pressures of 0.01 and 0.02 MPa was observed to surpass that obtained at 0.04 MPa, ranging from 4 to 4.5 L/m−2 h−1. The stability of flux was positively associated with the low membrane fouling resistance observed in the GDMBR system. Additionally, the GDMBR system provided remarkable efficiencies in removing the chemical oxygen demand (COD), biological oxygen demand (BOD), ammonia (NH4+-N), and total nitrogen (TN), with average removal rates of 82%, 80%, 83%, and 79%, respectively. The high biological activity and microbial community diversity within the sludge and biofilm are expected to enhance its biodegradation potential, thereby contributing to the efficient removal of contaminants. Notably, a portion of total phosphorus (TP) can be effectively retained in the reactor, which highlighted the promising application of the GDMBR process for actual fruit juice wastewater based on these findings.